Analysis of the Impact of Telemedicine on Health Care: A Review of the Scientific Literature from 2015-2020 - Michael Castillon-Herrera; Michael Cabanillas-Carbonell (Communications of International Proceedings, 2020)
Currently, people with reduced mobility, with some physical disability or people who are in remote areas, as well as in a situation of confinement, cannot receive medical attention in person. These problems can be solved through telemedicine. This research is a systematic review of the scientific literature and aims to determine the criteria to be considered for the analysis of the impact of telemedicine in medical care. For which 50 articles were systematized, collected from the databases of the IEEE Xplore, Scopus, Science Direct, Scielo. Having very favorable results about the impact of telemedicine in medical care and in the different fields related to medicine.
Keywords: "impact of telemedicine"; "medical assistance"; "telemedicine system”.